Sistem Pendukung Keputusan menggunakan Metode Servqual untuk Meningkatkan Kualitas Pelayanan Kinerja Aparatur Pemerintahan - Rahmiatun Nisa; Riki Andri Yusda; Wiwin Handoko (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Improving a service in an agency cannot be separated from several aspects that must be owned such as assurance, empathy, responsiveness, reliability and physical evidence. However, there are several obstacles in improving services at the Setia Janji sub-district office, such as less informative and less transparent. The purpose of this study is to create a decision support system using the servqual method to improve the quality of government apparatus performance services. This research applies the waterfall model to build a system with stages of analysis, design, implementation and testing. Analysis is carried out to find needs regarding the system created. While the design consists of an entity relationship diagram and interface design. Furthermore, the implementation stage was carried out at the Setia Jani sub-district office using a questionnaire referring to servqual with the number of research subjects was 201. Aspects of this study consist of care, physical service, responsiveness, physical reliability, and assurance. Testing the system uses a black box to see how far the functionality of this system is. Our findings are that improvements need to be made in services regarding assurance (communication, courtesy, communication, and security). In addition, our system has also been running well based on the results of black box testing. So that this system can be used of this district as a policy in making decisions to improve the performance of government apparatus services.